PEMANFAATAN KITOSAN SEBAGAI BAHAN DASAR PEMBUATAN EDIBLE FILM DARI PATI UBI JALAR KUNING - Ricki Mustapa; Fajar Restuhadi; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to obtained the best chitosanconcentration in making edible film from sweet potato starch. This research usedCompletely Randomized Design (CRD) with five treatments and threereplications. Data were obtained using analysis of variance (Anova) continued byDuncan’s New Multiple Range Test (DNMRT) test at 5%. The treatments in thisresearch was K (chitosan 2%), K2 (chitosan 3%), K3 (chitosan 4%), K4 (chitosan5%) and K5 (chitosan 6%). The results of analysis of variance showed that theused different concentration of chitosan was significantly affected on the degreeon thickness, resistance of water, transparency of the value, and water vaportransmission rate. The best treatment in this research was treatment of K5(chitosan 6%) with degree of thickness 0,20 mm, resistance of water 21,77%,transparency of the value 2,12, and water vapor transmission rate 0,02 g/m2/h.Keyword: sweet potato starch, chitosan, edible film.